Colorectal surgery: Surgical approaches and postoperative rehabilitation strategies - Canali, Bruna Vergani; Silveira , Laís Tinoco; Brito, Gabriele de Lima Gazani; Ribeiro, Nathalia Rodrigues; Mujahed, Guilherme Badawi Urio; Fernandes, Ana Carolina Shinkawa; Mujahed, Isaac Badawi Urio; Fiore, Denilson; Júnior, Ademar Bretas (Seven Editora, 2023)
Colorectal surgery is a multifaceted medical discipline that encompasses the treatment of various conditions, including colorectal cancer, inflammatory bowel diseases, and diverticulitis. This review article examines surgical approaches and post-operative rehabilitation strategies in this field of medicine. Concerning surgical approaches, we highlight laparoscopy and robotic surgery as alternatives to open surgery. Laparoscopy offers benefits such as shorter hospital stays and faster recovery, but the choice of surgical technique should be personalized, taking into account the complexity of the case and the surgeon's experience. Robotic surgery, while promising, faces challenges related to costs and the learning curve. Regarding post-operative rehabilitation strategies, we emphasize the importance of a multimodal approach, which integrates physical therapy, pain management, psychosocial support, proper nutrition, and early mobilization. Personalizing care based on the individual needs of the patient is crucial for a successful recovery. In conclusion, colorectal surgery requires carefully considered decisions and holistic care to achieve effective outcomes and improve patients' quality of life. Ongoing research and the evolution of techniques are essential for enhancing clinical practice in this field. Individualized care and interdisciplinary collaboration are key to ensuring the success of colorectal procedures. DOI:https://doi.org/10.56238/sevened2023.004-060